Practical application of a mixed active and passive heat acclimation protocol in elite male Olympic team sport athletes - Fenemor, S. P.; Driller, M. W.; Gill, N. D.; Mills, B.; Casadio, J. R.; Beaven, C. M. (Applied Physiology, Nutrition, and Metabolism, 2022)
To investigate effectiveness and retention of heat acclimation (HA) integrated within an elite rugby sevens team training program, 12 elite male rugby sevens athletes undertook 10 days of mixed active/passive HA across 2 weeks of normal training. Physiological and performance variables were assessed using a sport-specific, repeated high-intensity heat-response test pre-HA; after 5 days (mid-HA) and 10 days (post-HA); and 16 days post-HA (decay). Resting, submaximal, and end-exercise core temperatures were lower at mid-HA (=-0.26 °C; d = -0.47), post-HA (=-0.30 °C; d = -0.72), and decay (=-0.29 °C; d = -0.56), compared to pre-HA. Sweat rate was greater at post-HA compared to pre-HA (0.3 ± 0.3 L·h-1; d = 0.63). Submaximal heart rate (HR) was lower at mid- (-9 ± 4 bpm; d = -0.68) and post-HA (-11 ± 4 bpm; d = -0.90) compared to pre-HA. Mean and peak 6 s power output improved at mid-HA (83 ± 52 W; 112 ± 67 W; d = 0.47) and post-HA (125 ± 62 W; 172 ± 85 W; d = 0.72) compared to pre-HA. Improvements in HR and performance persisted at decay (d = 0.66). The initial 5 days of mixed-methods HA elicited many typical HA adaptations, with an additional 5 days eliciting further thermoregulatory, sudomotor, and performance improvements. Adaptations were well retained after 16 days of normal training, without any further heat stimulus. The trial was retrospectively registered with the Australian New Zealand Clinical Trials Registry (ACTRN12622000732785).